Occasional adverbs in the poetry of Dniepropetrovsk’s authors (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article is devoted to investigation of occasional adverbs in the poetry of Dniepropetrovsk’s authors. There are consideration of the semantico-derivation peculiarities, imaginable potential and stylistic phenomena connected with these innovations.
Keywords: occasionalism; author-individual adverb; adverbial innovation; word forming model; semantic group; expressive functional